Biodiversity and Culture: Study Case on Indigenous Land of Apurina (Brazil) - Risso, Luciene Cristina [UNESP] (Univ Valle, 2015)
This study aims to discuss the concept of biodiversity and propose a cultural breadth of the subject. To this end, we conducted literature reviews and interviews on the Apurina Indigenous Land (Amazonas, Brazil). Seventy six species were cited with different utilities. However, uses are closely linked with the symbologies attributed, confirming that biodiversity has a cultural sphere that must be respected and considered in policy proposals. Keywords: concept of biodiversity, indigenous communities, culture.
Keywords: Biodiversity and culture: study case on indigenous land of Apurina (Brazil)